Noisy poems - Bennett, Jill.; Sharratt, Nick (Oxford ; New York : Oxford Universtiy Press, 2005)
Contains a collection of twelve noisy poems for children designed to be read aloud.
Bulletin (Center for Children's books)
Bulletin (Center for Children's books), April 2009
2.9
K-3.
K-3
Keywords: Children's poetry, English; English poetry; English poetry